2016
DOI: 10.7448/ias.19.1.20995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a switch from tenofovir‐ to abacavir‐based antiretroviral therapy, with or without atazanavir, on renal function

Abstract: IntroductionTenofovir disoproxil fumarate (TDF)–associated renal dysfunction may abate when TDF is replaced with abacavir (ABC). The extent to which the third drug atazanavir contributes to renal dysfunction is unclear.MethodsA retrospective analysis was conducted on adults who had plasma viral load (pVL)<200 copies/mL for≥six months while receiving TDF/lamivudine (3TC) – or TDF/emtricitabine (FTC)–based antiretroviral therapy (ART), then switched to ABC/3TC while retaining the third drug in the ART regimen. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Renal function parameters also remained stable during the study period, even in the subgroup of patients who switched from a regimen containing TDF ( P <0.975). These findings differ from those of other studies on switching from TDF to ABC, which reported a slight increase in eGFR [ 28 , 29 ]. A possible explanation could be that around 50% of patients were on ABC/3TC before switching, and TDF-containing regimens only accounted for 26% of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Renal function parameters also remained stable during the study period, even in the subgroup of patients who switched from a regimen containing TDF ( P <0.975). These findings differ from those of other studies on switching from TDF to ABC, which reported a slight increase in eGFR [ 28 , 29 ]. A possible explanation could be that around 50% of patients were on ABC/3TC before switching, and TDF-containing regimens only accounted for 26% of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the ASSURE (A Simplification Study of Unboosted Reyataz with Epzicom) trial showed a nonsignificant improvement in eGFR after switching from TDF to abacavir (+0.8 vs. À1.3 in those who continued TDF), but significantly better evolution in tubular proteinuria [21]. A significant improvement in eGFR, albuminuria and phosphataemia was also found in a recent study where TDF was switched to abacavir, regardless of whether or not patients continued with atazanavir [22]. These differences in eGFR evolution were mainly based on different baseline patient characteristics, because the studies included patients without renal involvement.…”
Section: Discussionmentioning
confidence: 80%
“…Unexpectedly, higher ABC utilization was associated with CKD and higher D:A:D CKD risk scores, although this could be attributed to confounding by indication. Use of tenofovir has been linked to kidney disease [24] and individuals on tenofovir with decreasing renal function are likely to discontinue tenofovir [25] and be switched to ABC [26], a drug with no reported adverse effect on renal function. Changes over time and within regions in use of abacavir probably reflect marketing and availability of abacavir.…”
Section: Discussionmentioning
confidence: 99%